2021
DOI: 10.1186/s12906-020-03184-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a new thyrotropic drug isolated from Potentilla alba on the male reproductive system of rats and offspring development

Abstract: Background The dysfunction of the thyroid gland is a common medical condition. Nowadays, patients frequently use medicinal herbs as complementary or alternative options to conventional drug treatments. These patients may benefit from treatment of thyroid dysfunctions with Potentilla alba L. preparations. While it has been reported that Potentilla alba preparations have low toxicity, nothing is known about their ability to affect reproductive functions in patients of childbearing age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Furthermore, the same extract had an impact on the male rat reproductive system, resulting in a decrease in sperm motility and Leydig cell nucleus diameters and an increase in pyknotic nuclei and a higher number of pathological spermatozoa. Despite these observations, the authors concluded that the extract did not significantly affect rodent fertility or offspring development after healthy female impregnation [80].…”
Section: Toxicitymentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the same extract had an impact on the male rat reproductive system, resulting in a decrease in sperm motility and Leydig cell nucleus diameters and an increase in pyknotic nuclei and a higher number of pathological spermatozoa. Despite these observations, the authors concluded that the extract did not significantly affect rodent fertility or offspring development after healthy female impregnation [80].…”
Section: Toxicitymentioning
confidence: 92%
“…Others Aminoacids R [28] Fatty acids, e.g., palmic, stearic, linoleic, linolenic acid A, R [39,40] Polyprenols with 19-45 units A [41] Polysaccharides R [28] Sitosterol R [37,80] Sitosterol 3-O-β-D-glucoside (daucosterol) R [37,80] Micro-and macroelements, e.g., magnesium, calcium, potassium, iron, manganese, phosphorus, iodine R [28] *Structure not fully elucidated; A = aerial part; R = root and/or rhizome nylenediamine (DMPD + ), superoxide radical, and hydroxyl radical assays, was reported for water and methanol extracts obtained from rhizomes and roots of P. alba [36,45].…”
Section: Tanninsmentioning
confidence: 99%
“…Одночасно ця рослина містить природно збалансовану комбінацію мікроелементів: йоду, селе- Практикуючому ендокринологу /To Practicing Endocrinologists/ ну, цинку й магнію. Такі складові чинять комплексний вплив на ЩЗ [8,9]. Родіола рожева (Rhodiola Rosea), екстракт коренів і кореневищ цієї рослини, -це адаптоген, що підвищує опірність організму стресу, виснаженню, перевтомі.…”
Section: субклінічний гіпотиреоз: чи завжди потрібна замісна гормональна терапія?unclassified